PENINGKATAN KETERAMPILAN KARYAWAN DI PERUSAHAAN ADANA GULA SEMUT KULON PROGO - Tunggal, Arif Nuryono; Novitasari, Dwi (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
This study aims to to find out what obstacles were faced by the Adana sugar ant company in improving employee skills and to find out the efforts to improve employee skills at the Kulon Progo sugar ant Adana company. The method used in this research is qualitative method, where data collection uses interview and documentation. Before the data was collected, it was analyzed first and checked its validity through the triangulation method. The results of this analysis show that The results of this study indicate that the low barriers experienced by the adana gula semut kulon progo company are that most of its employees belong to the productive age and education level so that they do not have the desire to improve skills, so the skills of employees in the production department cannot be implemented. The role of managers is still too dominant so that there is no active participation of employees in participating in determining company decisions. Efforts to improve the performance of the kulon progo sugar ant adana company are by providing skills training either directly or sending employees to attend training organized by the kulonprogo regency industry and trade office. Employee training in the marketing department has been carried out by providing concepts and authority in planning, marketing preparation, news editing, election documentation, as well as collecting and consumer testimonials that will be used in the adana gula semut online store to several active things in leading daring stores which are very important by employees in marketing.